Recombinant SpTransformer proteins are functionally diverse for binding and phagocytosis by three subtypes of sea urchin phagocytes - Crow, Ryley S.; Shaw, Chloe G.; Grayfer, Leon; Smith, L Courtney (Frontiers in Immunology, 2024)
Introduction The California purple sea urchin, Strongylocentrotus purpuratus, relies solely on an innate immune system to combat the many pathogens in the marine environment. One aspect of their molecular defenses is the SpTransformer (SpTrf) gene family that is upregulated in response to immune challenge. The gene sequences are highly variable both within and among animals and likely encode thousands of SpTrf isoforms within the sea urchin population. The native SpTrf proteins bind foreign targets and augment phagocytosis of a marine Vibrio. A recombinant (r)SpTrf-E1-Ec protein produced by E. coli also binds Vibrio but does not augment phagocytosis. Methods To address the question of whether other rSpTrf isoforms function as opsonins and augment phagocytosis, six rSpTrf proteins were expressed in insect cells. Results The rSpTrf proteins are larger than expected, are glycosylated, and one dimerized irreversibly. Each rSpTrf protein cross-linked to inert magnetic beads (rSpTrf::beads) results in different levels of surface binding and phagocytosis by phagocytes. Initial analysis shows that significantly more rSpTrf::beads associate with cells compared to control BSA::beads. Binding specificity was verified by pre-incubating the rSpTrf::beads with antibodies, which reduces the association with phagocytes. The different rSpTrf::beads show significant differences for cell surface binding and phagocytosis by phagocytes. Furthermore, there are differences among the three distinct types of phagocytes that show specific vs. constitutive binding and phagocytosis. Conclusion These findings illustrate the complexity and effectiveness of the sea urchin innate immune system driven by the natSpTrf proteins and the phagocyte cell populations that act to neutralize a wide range of foreign pathogens.